Cerebral markers of neuroinflammation and neurodegeneration in hypertensive disorders during pregnancy - E. S. Taskina; I. V. Kibalina; V. A. Mudrov; S. O. Davydov (Медицинская иммунология, 2025)
Preeclampsia/eclampsia during pregnancy and postpartum are the major risk factors for maternal and infant morbidity and mortality worldwide. At the same time, more than 70% of maternal deaths are of neurological origin, i.e., eclampsia, cerebral edema, intracranial hemorrhage and stroke. Generalized endothelial dysfunction caused by placental antiangiogenic factors leads to increased permeability of the blood-brain barrier and impaired autoregulation of cerebral circulation. Previous studies have shown that preeclampsia increases the risk of cerebrovascular and cardiovascular diseases, as well as cognitive impairments, up to evolving dementia in the future. According to a recently proposed neuropathophysiological hypothesis, preeclampsia is considered proteinopathy with impaired autophagy, thus contributing to brain depositions of wrongly folded pathological protein aggregates and antibodies to these proteins. Preclinical and clinical studies have shown that markers of neuroinflammation and neurodegeneration may reflect brain damage before the onset of severe neurological symptoms. However, is not entirely clear if these results correlate with long-term neurological complications. Over recent years, a certain understanding of preeclampsia pathophysiology in a broader sense has been gained. However, etiology and mechanisms of development of central nervous system dysfunction in this disease remain relevant for studies. A detailed systematic analysis of modern literature has been carried out, concerning the search for neuroinflammation and neurodegeneration markers in hypertensive pregnancy-associated disorders. The presented study used the following information databases: PubMed, Scopus, eLibrary, Cochrane Library, MEDLINE for the period from January 2015 to December 2024. This literature review provides information on pathogenetic role of the following neural biomarkers in preeclampsia: monocyte chemotactic protein 1 (MCP-1), brain-derived neurotrophic factor (BDNF), fractalkine (CX3CL1), neurospecific enolase (NSE), S100 calcium-binding protein B (S100B), visinin-like protein-1 (VILIP-1), tau protein (tai), phosphorylated tau protein for threonine 181 (p-tau181), a-synuclein (a-syn), amyloid b-40/42 (A 40/42), glial fibrillary acid protein (GFAP), light chains of neurofilaments (NfL). Usage of appropriate cerebral biomarkers will enable identification of patients at high risk for severe cerebral complications, optimization of their management and treatment during pregnancy, and development of effective strategies to prevent the development of neurological changes in the future.